Games theory and mediation of information: A proposal of strategic contribution to organizations - De Oliveira, Heloá Cristina Camargo; De Souza, Juliete Susan Ferreira; Valentim, Marta Lígia Pomim [UNESP]; De Almeida, Oswaldo Francisco [UNESP] (University Library System, University of Pittsburgh, 2018)
Objective. The purpose is to discuss the role that mediation of information can have in the context of Game Theory, which focuses refers to the concept of coopetition. It presents some aspects that can be pertinent for organizations to suit the reality of the current market, focusing on the mediation of information from the perspective of Game Theory. Method. It presents a theoretical rescue of game theory with regard to sharing of information and knowledge, and of the mediation and appropriation of information. Results. After the theoretical reviews, it was possible to approach the applicability of Game Theory in the context of mediation of information and information appropriation, in order to demonstrate the potential benefits of this union. It is concluded that mediation can not only be used in conjunction with the Theory of Games, but also significantly contribute to your application in a full and beneficial way for the parties involved.
A teoria dos jogos e a mediação da informação: Uma proposta de contribuição estratégica para organizações
Keywords: Game Theory; Information appropriation; Mediation of information; Organizational environments